Trade in a "green growth" development strategy global scale issues and challenges - Jaime de Melo (Fondazione Eni Enrico Mattei (FEEM), 2012)
The paper surveys the state of knowledge about the trade-related environmental consequences of a country's development strategy along three channels: (i) direct trade-environment linkages (overexploitation of natural resources and trade-related transport costs);(ii) virtual trade in emissions resulting from production activities; (iii) the product mix attributes of a green-growth strategy (environmentally preferable products and goods for environmental management). Main conclusions are the following. Trade exacerbates over-exploitation of natural resources in weak institutional environments, but there is little evidence that differences in environmental policies across countries have led to significant pollution havens. Trade policies to level the playing field would be ineffective and result in destructive conflicts in the WTO. Lack of progress at the Doha round suggests the need to modify the current system of global policy making.
Keywords: F18; Q56; 330; Environmental Goods; Natural Resources; Green Growth; Trade and Climate